2005
DOI: 10.1124/dmd.105.004903
|View full text |Cite
|
Sign up to set email alerts
|

IN VITRO METABOLISM OF THE CALMODULIN ANTAGONIST DY-9760e (3-[2-[4-(3-CHLORO-2-METHYLPHENYL)-1-PIPERAZINYL]ETHYL]-5,6-DIMETHOXY-1-(4-IMIDAZOLYLMETHYL)-1H-INDAZOLE DIHYDROCHLORIDE 3.5 HYDRATE) BY HUMAN LIVER MICROSOMES: INVOLVEMENT OF CYTOCHROMES P450 IN ATYPICAL KINETICS AND POTENTIAL DRUG INTERACTIONS

Abstract: DY-9760e, 3-[2-[4-(3-chloro-2-methylphenyl)-1-piperazinyl]ethyl]-5,6-dimethoxy-1-(4-imidazolylmethyl)-1H-indazole dihydrochloride 3.5 hydrate (Fig. 1), is a novel calmodulin antagonist being developed to treat acute ischemic stroke. It inhibits calmodulin-dependent enzymes and in so doing exerts neuroprotective effects in animals with induced strokes (Sugimura et al., 1997;Sato et al., 1999Sato et al., , 2003Sato et al., , 2004Fukunaga et al., 2000;Takagi et al., 2001;Hashiguchi et al., 2003). In experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Therefore, the discovery of more-efficient drugs for the treatment of VaD is of great significance. We previously reported that a calmodulin antagonist, 3-[2-[4-(3-chloro-2-methylphenyl)-1-piperazinyl]­ethyl]-5,6-dimethoxy-1-(4-imidazolylmethyl)-1H-indazole dihydrochloride 3.5 hydrate (DY-9760e), could reduce the infarct volume, diminish blood–brain barrier (BBB) breakdown, and suppress the elevated signal intensities present in the cortical region of the ipsilateral hemisphere in T2-weighted magnetic resonance imaging (MRI) studies. , Moreover, DY-9760e was capable of reducing BBB breakdown in a brain ischemia model by inhibition of calpain activation, calcium- and calmodulin-dependent nitric synthase activation, and protein tyrosine nitration. 3-[2-[4-(3-Chloro-2-methylphenyl)-1-piperazinyl]­ethyl]-5,6-dimethoxyindazole (DY-9836), a pharmacologically active metabolite of DY-9760e, does not interfere with the metabolism of other drugs in liver; thus, it seems more attractive than DY-9760e for clinical application, with great potential for the treatment of VaD. Nevertheless, low water solubility and poor pharmakinetics of DY-9836 (DY) restrict its further application.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the discovery of more-efficient drugs for the treatment of VaD is of great significance. We previously reported that a calmodulin antagonist, 3-[2-[4-(3-chloro-2-methylphenyl)-1-piperazinyl]­ethyl]-5,6-dimethoxy-1-(4-imidazolylmethyl)-1H-indazole dihydrochloride 3.5 hydrate (DY-9760e), could reduce the infarct volume, diminish blood–brain barrier (BBB) breakdown, and suppress the elevated signal intensities present in the cortical region of the ipsilateral hemisphere in T2-weighted magnetic resonance imaging (MRI) studies. , Moreover, DY-9760e was capable of reducing BBB breakdown in a brain ischemia model by inhibition of calpain activation, calcium- and calmodulin-dependent nitric synthase activation, and protein tyrosine nitration. 3-[2-[4-(3-Chloro-2-methylphenyl)-1-piperazinyl]­ethyl]-5,6-dimethoxyindazole (DY-9836), a pharmacologically active metabolite of DY-9760e, does not interfere with the metabolism of other drugs in liver; thus, it seems more attractive than DY-9760e for clinical application, with great potential for the treatment of VaD. Nevertheless, low water solubility and poor pharmakinetics of DY-9836 (DY) restrict its further application.…”
Section: Introductionmentioning
confidence: 99%
“…Training and test set compounds for this model are shown in Table 18. [67,[124][125][126][127][128][129][130][131][132] (S)-verapamil ((S)-19) [124], nifedipine (29) [124], astemizole (110) [107], and quinidine (166) [124] were employed as additional test set compounds. (Fig.…”
Section: Ligand-based General Model For P450 3a4 Substratesmentioning
confidence: 99%